Tren Penggunaan Literasi Digital di Sekolah Dasar (Elementary School): Bibliometrik Analisis - Lina Fadilla; Amirudin Amirudin; Hasan Sastra Negara (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to identify and analyze research trends related to the use of digital literacy in primary education, as well as to explore potential directions for future research. Digital literacy is an essential 21st-century competency that should be developed from the primary school level, in line with the increasing integration of technology in teaching and learning processes. However, systematic studies that map research trends, focal areas, and thematic developments in digital literacy within primary education remain relatively limited, while its implementation in primary schools has not yet been fully optimized. This research employs a Systematic Literature Review (SLR) approach combined with bibliometric analysis based on PRISMA guidelines. The data were obtained from 50 publications indexed in the Scopus database between 2021 and 2025. Following a rigorous selection process based on inclusion criteria, 13 articles were further analyzed using VOSviewer software version 1.6.20. The findings indicate that publication trends related to digital literacy in primary education are fluctuating, with a significant increase and peak in publications in 2025. Indonesia emerged as the country with the highest contribution to publications in this field. Keyword mapping analysis reveals that the main research themes include digital literacy, media literacy, ICT literacy, and the integration of digital literacy into instructional strategies. Meanwhile, topics related to personalized learning and digital safety remain relatively underexplored, highlighting promising opportunities for future research.